Toward wear-resistive, highly durable and high performance triboelectric nanogenerator through interface liquid lubrication. (June 2020) - Wu, Jian; Xi, Yinhu; Shi, Yijun
Abstract: Triboelectric nanogenerator (TENG) has been proved as a powerful approach to harvest ambient mechanical energy for many technological applications. However, the service lifetime, stability and robustness of TENG are a challenge owing to the wearing and surface degradation. In this manuscript, liquid lubrication is introduced for the first time to increase the anti-wear property of TENG. The influence of the lubricant layer between the surfaces on TENG outputs is studied. It is surprising to find that proper liquid lubrication can not only provide a super wear-resistive TENG, but also can increase the electric outputs. In comparison to a slide-mode TENG with solid-solid contact, the service life of TENG can be greatly improved through liquid lubrication and there is no detected wear even after 36, 000 cycles of operation. Specially, the open-circuit voltage and short-circuit current of squalane-lubricated TENG can be both more than 3 times of the unlubricated TENG. For unlubricated TENG, a transfer polymer film adheres to the harder material surface and reduces the contact effectiveness. Liquid lubrication is able to avoid the formation of the transfer film, increase the effective solid-solid contact area and squeeze the air at the interface, thus giving rise to higher electric outputs. Our study opens a new approach for extending the lifetime and stability of TENGs. Graphical abstract: Image 1 Highlights: Liquid lubrication is applied for the first time to increase the service life of TENG. The voltage and current of lubricated TENG can be both more than 3 times of the unlubricated TENG. For unlubricated TENG, a transfer polymer film adheres to the harder surface and reduces the contact effectiveness. Liquid lubrication avoids the transfer film formation. Liquid lubrication increases the effective solid-solid contact area and squeezes the air at the interface.